Possible causes of serous nipple discharge - G. Kh. Khanafiyev; S. A. Berzin; U. Yu. Maltseva; A. E. Mazur (ABV-press, 2014)
The paper considers the possible causes of serous nipple discharge. The study enrolled 62 patients aged 35 to 60 years who visited a physician for serous nipple discharge after long-term ineffective treatment with various drugs. The blood level of placental lactogen and the uterus as a possible cause of its nonpregnancy appearance were studied in all the examined.